2019
DOI: 10.1021/acs.jafc.9b05174
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Key Aroma Compounds in Pellets of Different Hop Varieties (Humulus lupulus L.) by Means of the Sensomics Approach

Abstract: The use of hops in beer brewing is mainly based on its content of bitter acids and aroma compounds. Due to the loss of volatile odorants during wort boiling, the so-called dry hopping is a possibility to intensify the hoppy aroma in the final beer. To clarify the potential of different hop varieties for aroma modulation of beer via dry hopping, key aroma compounds of three different hop varieties were characterized using the sensomics approach. Aroma extract dilution analysis revealed 41 aroma-active compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 38 publications
0
44
1
Order By: Relevance
“…The highest concentration of organic acids was obtained in the L. brevis beer (942 ± 11 mg/L acetic, 2598 ± 56 mg/L lactic, and 196 ± 14 mg/L succinic acid, Supplementary Table S3) followed by the L. plantarum beer (89 ± 26 mg/L acetic, 1792 ± 94 mg/L lactic, and succinic acid below detection, Supplementary Table S3), while no lactic acid or succinic acid and only a limited amount of acetic acid (31 ± 4 mg/L, Supplementary Table S3) was generated in the reference beer. Lactic acid is associated with acidity and sourness (Van Oevelen et al, 1976) and has a reported taste threshold of 400 mg/L (Engan, 1974). Acetic acid is associated with acidity, sour (Engan, 1974) and vinegary flavors (Van Oevelen et al, 1976) and has a reported sensory threshold of 200 mg/L (Engan, 1974).…”
Section: Metabolite Composition and Sensory Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The highest concentration of organic acids was obtained in the L. brevis beer (942 ± 11 mg/L acetic, 2598 ± 56 mg/L lactic, and 196 ± 14 mg/L succinic acid, Supplementary Table S3) followed by the L. plantarum beer (89 ± 26 mg/L acetic, 1792 ± 94 mg/L lactic, and succinic acid below detection, Supplementary Table S3), while no lactic acid or succinic acid and only a limited amount of acetic acid (31 ± 4 mg/L, Supplementary Table S3) was generated in the reference beer. Lactic acid is associated with acidity and sourness (Van Oevelen et al, 1976) and has a reported taste threshold of 400 mg/L (Engan, 1974). Acetic acid is associated with acidity, sour (Engan, 1974) and vinegary flavors (Van Oevelen et al, 1976) and has a reported sensory threshold of 200 mg/L (Engan, 1974).…”
Section: Metabolite Composition and Sensory Analysismentioning
confidence: 99%
“…Lactic acid is associated with acidity and sourness (Van Oevelen et al, 1976) and has a reported taste threshold of 400 mg/L (Engan, 1974). Acetic acid is associated with acidity, sour (Engan, 1974) and vinegary flavors (Van Oevelen et al, 1976) and has a reported sensory threshold of 200 mg/L (Engan, 1974). Both lactic and acetic acid were well above reported sensory thresholds in the L. brevis beer, which corresponds well with this beer being perceived as significantly higher than the L. plantarum and the reference beer in acidic taste in the sensory analysis ( Figure 5C and Supplementary Table S4).…”
Section: Metabolite Composition and Sensory Analysismentioning
confidence: 99%
“…Every 24 hours, the concentrations of eight different odorants (ethyl 2-methylbutanoate, ethyl 3-methylbutanoate, ethyl methylpropanoate, geraniol, linalool, methyl 2-methylbutanoate, myrcene, and propyl 2-methylbutanoate) were determined, which have already been identified as important odorants in hops and dry-hopped alcohol-free beer. 1,10 For geraniol, linalool, and myrcene, the maximal transfer rates were reached after 2-3 days (Figure 1). Afterwards, a decline in concentrations was observed.…”
Section: Time Dependency Of the Transfer Of Odorants During Dry-hopmentioning
confidence: 96%
“…By applying the molecular sensory science concept, linalool, myrcene, 3-methylbutanoic acid, and geraniol were identified as important aroma-active compounds in hop varieties. [1][2][3] For some hops, variety-specific odorants were identified like ethyl 2-methylbutanaote in Huell Melon or 4-mercapto-4-methylpentan-2-one in US varieties like Cascade, Citra, and Eureka. 4 Especially by late-or dry-hopping, higher concentrations of these hop odorants can be achieved in the final product.…”
Section: Introductionmentioning
confidence: 99%
“…Hallertauer Mandarina Bavaria hop pellets type 90, harvest year 2015, were provided by Hopsteiner (Mainburg, Germany). Identification and quantitation of odorants in this batch have already been performed in a previous study (Brendel et al 2019). Hop extracts were also provided by Hopsteiner: Alpha extract contained 20.0 ± 1.0% α-acids.…”
Section: Hop Samplesmentioning
confidence: 99%